UPAYA PEMBENTUKAN KARAKTER RELIGIUS DAN KEPRIBADIAN SANTRI MELALUI PENGABDIAN KEPADA KIYAI DI LEMBAGA PONDOK PESANTREN MIFTAHUL ULUM SUMBERJATI DESA BUNGBARUH KECAMATAN KADUR KABUPATEN PAMEKASAN - Maulana Mohammad Fahmiy; Azhar Haq; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Character and personality are very important and fundamental things in human life. Character and personality must be built and shaped, because it is related to human values related to human activities both related to God, self, others, and the environment. One of the efforts to establish religious character in the world of pesantren is through the devotion of a santri to the chaplain. Students who serve will be more formed religious character and personality, because by serving students can interact directly with also be able to obtain knowledge directly from the cleric and not only theory but directly with his practice. In this study researchers used qualitative research methods with the type of case study research. Researchers used data collection techniques such as observation, interviews, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. While in checking the validity of the data, researchers used several techniques, namely perseverance, triangulation, and peer discussions. The results of this study about the efforts to form religious character and personality of students through serving the clerics, namely guiding directly both theory and practice and instilling and discerning the 4 exemplary qualities of the Prophet.